Peran Kepuasan Kerja dan Keterlibatan Karyawan sebagai Pemediasi Pengaruh Lingkungan Kerja terhadap Produktivitas Karyawan - Ngangi, Melisa (Universitas Sam Ratulangi, 2019)
This study aims to determine whether the work environment, job satisfaction and work involvement affect work productivity, and whether the work environment influences employee productivity with job satisfaction and employee involvement as mediators. Research results show that (1) Work Environment has a significant effect on Job Satisfaction; (2) Work Environment has a significant effect on Employee Engagement; (3) Job Satisfaction does not have a significant effect on Employee Productivity; (4) Employee Engagement does not have a significant effect on Employee Productivity; (5) Work Environment has a significant effect on Employee Productivity; (6) Job Satisfaction does not significantly influence the mediation of the Work Environment towards Employee Productivity; (7) Employee involvement does not have a significant effect as mediating the Work Environment towards Employee ProductivityKeywords: Work environment, employee engagement, job satisfaction, employee productivity